Tunable inverted gap in monolayer quasi-metallic MoS2 induced by strong charge-lattice coupling - Xinmao Yin; Qixing Wang; Liang Cao; Chi Sin Tang; Xin Luo; Yujie Zheng; Lai Mun Wong; Shi Jie Wang; Su Ying Quek; Wenjing Zhang; Andrivo Rusydi; Andrew T. S. Wee (Nature Communications, 2017)
MoS2 exhibits multiple electronic properties associated with different crystal structures. Here, the authors observe inverted and fundamental gaps through a designed annealing-based strategy, to induce a semiconductor-to-metal phase transition in monolayer-MoS2 on Au, facilitated by interfacial strain and electron transfer from Au to MoS2.